Ad Disclosure vs. Ad Recognition: How Persuasion Knowledge Influences Native Advertising Evaluation. Issue 1 (2nd January 2019) - Jung, A-Reum; Heo, Jun
Abstract: This study investigated how ad disclosure and ad recognition predict the effectiveness of native advertising in relation to persuasion knowledge. Two experimental studies revealed that evaluation of a natively formatted ad was influenced by knowledge of social media advertising tactics and ad recognition, rather than the explicitness of ad disclosure. Findings suggest that recognition of the natively formatted ad was triggered mostly by prior experience with social media ads, rather than ad disclosure. These findings also suggest the limited effects of ad disclosure and signify the importance of consumer education. Theoretical and practical implications are discussed.